Identification of Fusarium fujikuroi Isolated from Barnyard Grass and Possibility of Inoculum Source of Bakanae Disease on Rice - Hyo-Won Choi; Wan Gyu Kim; Sung Kee Hong,; Yong-Hwan Lee; Young Kee Lee; Se-Chul Chun (Research in Plant Disease, 2011)
Bakanae disease symptom were observed in barnyard grass in paddy field in Heanam, Jeonnam. The infected plants were blighted and white mass of spore were formed on the stem. Fusarium species were isolated from infected stem and the isolates were identified as Fusarium fujikuroi based on their morphological and molecular characteristics. The isolates of F. fujikuroi were assigned to reference of F. fujikuroi among related Fusarium species based on the translation elongation factor 1-alpha gene sequence. Pathogenicity of the fungal isolates was confirmed on seedlings of rice and barnyard grass by artificial inoculation. The results indicated that barnyard grass can be inoculum source of Bakanae disease on rice. Thus, effective weed management is necessary to Bakanae disease control and healthy seed production.